Poetic justice, legal justice (or: what poets and lawyers might have in common) / Justiça poética, Justiça legal (ou: o que poetas e advogados podem ter em comum) - Blumenthal, Michael C. (REVISTA QUAESTIO IURIS, 2015)
DOI: http://dx.doi.org/10.12957/rqi.2015.16919 Trabalho enviado em 06 de junho de 2015. Aceito em 14 de junho de 2015. <p class="Paragraph SCX28274169" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Abstract <p class="Paragraph SCX28274169" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;"> <p class="Paragraph SCX28274169" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">In this paper, the author introduces its main subject , which is the idea of justice in both poetry and law, by comparing the role of both poets and lawyers in the the movement of reinforcing the morality in a society. To analyze this idea, the professor uses the language of myth, which has a great deal in common with both pursuits. By telling the myth of Philoctetes, the author introduces that both poets and lawyers have in common a certain crave after justice, and what differs each one is the manner of satisfying this craving. Then, by comparing the characters of the myth with poets and lawyers, he describes the disparities between the both. Then, by analyzing and comparing the character Philoctetes with the poetic persona of the poem used as an example, he shows that the poetic subject tends to be an individual who suffered injustices, suffered from loneliness and distress, and when seeking for a better solution to his pain, reveals his longing for justice. The lawyer, in his turn, is someone with a great sense of a job to do, and wants to get it done. Even if he feels a sincere attachment to the ideals of justice, he is not usually someone who has been gravely wounded by injustice. Like the kind of artist we all admire, he embodies in his work, and in his life, something of the rectifying urge. <p class="Paragraph SCX28274169" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;"> <p class="Paragraph SCX28274169" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Keywords: poets, lawyers, law, justice, poetic justice, myth Resumo Neste artigo, o autor apresenta o seu tema principal, que é a idéia de justiça, tanto a poesia e no direito, comparando-se o papel de ambos os poetas e advogados no movimento de reforçar a moralidade na sociedade. Para analisar essa idéia, o professor usa a linguagem do mito, que tem muito em comum com ambas as atividades. Ao contar o mito de Philoctetes, o autor introduz que ambos os poetas e os advogados têm em comum um certo anseio por justiça, e o que difere cada um é a maneira de satisfazer esse desejo. Em seguida, comparando os personagens do mito com poetas e os advogados, ele descreve as disparidades entre os dois. Então, analisando e comparando o personagem Philoctetes com o eu lírico do poema usado como um exemplo, ele mostra que o sujeito poético tende a ser um indivíduo que sofreu injustiças, sofria de solidão e angústia, e quando procurando uma melhor solução para sua dor, revela seu desejo de justiça. O advogado, por sua vez, é alguém com um grande sentido de um trabalho a fazer, e quer fazê-lo. Mesmo que ele sinta um apego sincero aos ideais de justiça, ele não é geralmente alguém que tenha sido gravemente ferido pela injustiça. Como o tipo de artista que todos nós admiramos, ele incorpora em seu trabalho e em sua vida, algo do desejo de retificação. Palavras-chave: poetas, advogados, direito, justiça, justiça poética, mito.